2008
DOI: 10.1142/s0217979208047389
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Impact Analysis of Side Kick in Taekwondo

Abstract: Taekwondo is a martial art form and sport that uses the hands and feet for attack and defense. Taekwondo basic motion is composed of the breaking, competition and poomsea motions. The side kick is one of the most important breaking motions. The side kick with the front foot can be made in two steps. In the first step, the front foot is extended forward from the back stance free-fighting position. For the second step, the rear foot is followed simultaneously. Then, the side kick is executed while the entire bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Rotation of the body and pivoting on one leg is an essential component in all of these kicking skills. Previous studies found that elite TKD athletes could turn and kick at high speeds (5.2m/s to 16.26m/s) and they generate huge amount of striking forces (390.7N to 661.9N) without loosing balance (Pieter and Pieter, 1995; Lee et al, 2008). In addition to turning and kicking, TKD practitioners adjust their body position and distance to the opponent frequently by stepping to different directions during competitions in order to score points.…”
Section: Introductionmentioning
confidence: 99%
“…Rotation of the body and pivoting on one leg is an essential component in all of these kicking skills. Previous studies found that elite TKD athletes could turn and kick at high speeds (5.2m/s to 16.26m/s) and they generate huge amount of striking forces (390.7N to 661.9N) without loosing balance (Pieter and Pieter, 1995; Lee et al, 2008). In addition to turning and kicking, TKD practitioners adjust their body position and distance to the opponent frequently by stepping to different directions during competitions in order to score points.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity of kicks was reported in 31 instances for the roundhouse kick [ 2 , 12 , 21 , 26 , 28 , 29 , 31 , 32 , 42 , 43 , 44 , 46 , 47 , 53 , 57 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], 10 for the roundhouse kick to the head [ 24 , 59 , 66 , 67 , 75 , 76 , 77 , 78 , 79 , 80 ], 8 for the side kick [ 13 , 25 , 28 , 57 , 65 , 71 , 72 , 81 , 82 ], 19 for the front kick [ 11 , 45 , 55 , 57 , …”
Section: Resultsmentioning
confidence: 99%
“… Means and standard deviations of peak linear foot velocity (m/s) for kicking strikes in combat sports: ( a ) roundhouse kick, ( b ) roundhouse kick to the head; ( c ) side kick, ( d ) front kick, ( e ) back kick, ( f ) axe kick. Where an error bar is absent, only a maximum velocity value was reported [ 2 , 11 , 12 , 13 , 21 , 23 , 24 , 25 , 26 , 28 , 29 , 31 , 32 , 42 , 43 , 45 , 46 , 47 , 50 , 52 , 55 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoroughly understanding how a human responds in an impulsive environment is essential to prevent injuries [2,3]. Many improvements have been accomplished through various studies and analyses, and these results have been applied to new aircraft designs [4].…”
Section: Introductionmentioning
confidence: 99%